2019
DOI: 10.1108/ijse-03-2018-0118
|View full text |Cite
|
Sign up to set email alerts
|

Citizens and expatriates satisfaction with public services in Qatar – evidence from a survey

Abstract: Purpose The purpose of this paper is to analyze citizens’ and expatriates’ satisfaction with public service delivery in Qatar, one of the world’s highest per capita incomes countries. Design/methodology/approach The author uses a 2017 survey conducted in Qatar among both Qatari and expatriates’ respondents. The scientifically grounded sample consisted of 1,356 respondents, who were 18 years of age and older. The data were collected through a face-to-face survey. The focus was on citizen satisfaction with bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
3
0
1
Order By: Relevance
“…Performance measurement theme assessed service delivery by government and private sector respectively. In Quatar, it was found that there was a higher level of satisfaction in public services compared to independent schools (Abdelkader Benmansour, 2019). Furthermore, Innovativeness, Good governance, Customer satisfaction and Quality healthcare were themes that if applied, would lead to quality service delivery while Corruption and Bureaucracy negatively affected service delivery.…”
Section: Sd Research Themesmentioning
confidence: 99%
See 1 more Smart Citation
“…Performance measurement theme assessed service delivery by government and private sector respectively. In Quatar, it was found that there was a higher level of satisfaction in public services compared to independent schools (Abdelkader Benmansour, 2019). Furthermore, Innovativeness, Good governance, Customer satisfaction and Quality healthcare were themes that if applied, would lead to quality service delivery while Corruption and Bureaucracy negatively affected service delivery.…”
Section: Sd Research Themesmentioning
confidence: 99%
“…No. of Articles Authors 1 Africa 11 (Abdulkareem & Mohd Ramli, 2021;Adaku et al, 2018;Akinboade et al, 2013;Biljohn & Lues, 2019;Falisse & Leszczynska, 2022;Kuye & Akinwale, 2020;Li et al, 2019;Masiya et al, 2019;Musenze & Mayende, 2019;Phiri, 2017;Tassabehji et al, 2019;Yusheng & Ibrahim, 2019) 2 Asia 20 (Abdullah et al, 2016;Anwer Anwer et al, 2016;Aruan et al, 2018;Abdelkader Benmansour, 2019;Chakraborty et al, 2021;Jain Gupta & Suri, 2017;Hwang et al, 2021;Kekez et al, 2018;Lanin & Hermanto, 2019;Nayak & Samanta, 2014;Nguyen et al, 2017;Rahman et al, 2021;Saxena, 2017;Siddiquee, 2016;Siddiquee, 2019;Siddiquee & Xavier, 2020;Smith, 2020;ur…”
Section: S/n Continentunclassified
“…Romero-Subia et al [18] argues that the effectiveness of the government's operations is greatly influenced by the quality of the public services it offers. Numerous studies, for example, Abdelkader Benmansour [44], indicate that a citizen's satisfaction with the quality of public services plays a crucial role in influencing that person's level of trust in the government. According to Mishra and Attri [45], citizens' confidence in the government increased due to using public services and interacting with the government.…”
Section: Citizen's Satisfaction With the Quality Of Public Services A...mentioning
confidence: 99%
“…[77], and the fourth item was "How satisfied are you with the nine elements listed below, such as housing, health care services, etc.?" [44]. The transparency of government was measured with 4-items, the first three items which are "Plans and programs for government administration are carried out openly", "Transparency is maintained throughout the administrative procedures", and "Residents can monitor development and general administration if enough information is made available" [81].…”
Section: Study Measuresmentioning
confidence: 99%